THE ROLE OF INNOVATIVE TECHNOLOGIES IN AGRICULTURAL MANAGEMENT (European Journal of Economics, Finance and Business Development, 2025)
Investment is one of the necessary conditions for effective and sustainable development of agriculture. This article talks about the ways of attracting investments in agriculture and their effective use and it talks about the construction of innovative projects.